IMPROVING THE ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR HUMAN RESOURCE DEVELOPMENT IN THE CIVIL SERVICE: INTERNATIONAL EXPERIENCE AND LESSONS FOR UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article presents a comparative analysis of the organizational and economic mechanisms for human resource development in the civil service, based on international experience and Uzbekistan’s national context. The research explores the degree of institutional linkage between mechanisms of evaluation, development, and incentives. The study analyzes the results of a quota-stratified survey (n=921) conducted in February 2026 in the Republic of Karakalpakstan, Namangan, Andijan, and Tashkent regions, and the city of Tashkent, covering employees in the economy, social sector, tax system, and representatives of the mahalla institution. The methods used include institutional analysis, comparative approach, and normative-legal review. Findings show that 15.3% of employees in organizations with formal evaluation systems reported not receiving training recommendations aligned with their performance results, while 33.7% cited lack of time for professional development. Based on this, an integrated organizational-economic approach to human resource development is proposed.
Keywords: civil service, human resource development, organizational mechanisms, economic incentives, evaluation system, meritocracy, HR analytics.